2017
DOI: 10.1002/mabi.201700029
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Poly‐l‐Glutamate‐Based Complexes for pDNA Delivery

Abstract: Due to the polyanionic nature of DNA, typically cationic or neutral delivery vehicles have been used for gene delivery. As a new approach, this study focuses on the design, development, and validation of nonviral polypeptide-based carriers for oligonucleotide delivery based on a negatively charged poly-l-glutamic acid (PGA) backbone partly derivatized with oligoaminoamide residues. To this end, PGA-derivatives modified with different pentameric succinyl tetraethylene pentamines (Stp 5 ) are designed. Optionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…35 For assays with saRNA we made the specic choices of poly(b-amino-ester)s (PBAEs) as the polycations as these have been shown to be effective delivery agents for saRNA in pre-clinical studies, 36 and poly(glutamic acid)s (PGAs) owing to their known safety prole and ready availability. [37][38][39] The versatility of the routes to PBAEs and the ease of end-group modication via the nal capping stage has been exploited by many groups, with a range of chemistries adopted and with or without cell-targeting agents. [40][41][42] In addition, Green et al have shown that the end-groups of PBAEs can modulate transfection activity of delivered nucleic acids in a range of cell lines, 43 while substitution of more hydrophobic regions in the PBAE backbone can alter biodistribution and efficacy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…35 For assays with saRNA we made the specic choices of poly(b-amino-ester)s (PBAEs) as the polycations as these have been shown to be effective delivery agents for saRNA in pre-clinical studies, 36 and poly(glutamic acid)s (PGAs) owing to their known safety prole and ready availability. [37][38][39] The versatility of the routes to PBAEs and the ease of end-group modication via the nal capping stage has been exploited by many groups, with a range of chemistries adopted and with or without cell-targeting agents. [40][41][42] In addition, Green et al have shown that the end-groups of PBAEs can modulate transfection activity of delivered nucleic acids in a range of cell lines, 43 while substitution of more hydrophobic regions in the PBAE backbone can alter biodistribution and efficacy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[157] Other small moieties used for biopolymer modification include quaternary amines, [56,73,[158][159][160] spermine, [63,161,162] piperazine, [163] cystamine, [69] and succinyl tetraethylene pentamine. [164] Moreover,the polymer backbone itself can be chemically modified to modulate its intrinsic charge.C hitosan, which is positively charged only at acidic pH, can be trimethylated at its primary amines resulting in ap ositive charge over ab roader pH range. [55,[165][166][167][168] In case of proteins such as albumin, methyl esterification of carboxyl groups decreases negative charge and renders the overall protein positively charged and well-suited for DNAc ondensation.…”
Section: à Modification Required For Dna Condensationmentioning
confidence: 99%
“…[233] Throughout the maturation of the endosomes,t he pH decreases from physiological pH 7.4 to pH % 6.5 in the early endosome,pH% 6.0 in the late endosome and pH % 5.0 in the lysosome due to the activity of membrane-bound ATPase pumps (proton pumps), which pump protons across the endosome and lysosome membrane into the vesicle interior through ATPh ydrolysis. [234] Thep resence of cationic poly-mers,s uch as PEI, [91,142,144,147,152,235] polyamidoamine, [151] succinyl tetraethylene pentamine, [164] spermine, [89,139-141, 161, 162, 236] and imidazole-containing molecules,s uch as histidine, [83,90] can all lead to endosomal rupture via the "proton-sponge" effect. This effect is associated to the large buffering ability of these molecules due to proton binding,w hich leads to more protons being pumped.…”
Section: Designing Carriers That Enable Endosomal Escapementioning
confidence: 99%